Burden, quality of life, and coping of caregivers of obsessive-compulsive disorder and healthy controls - Behura, Sushree S.; Mahapatra, Jashobanta (International Journal Of Community Medicine And Public Health, 2025)
Background: Caregiver burden refers to the detrimental effects of caregiving on a caregiver’s health, well-being, quality of life (QoL), and adaptation to challenging circumstances. The trajectory of any chronic mental disease is determined by the burden of morbidity, treatment costs, and the caregivers’ responsibilities during the rehabilitation process. Caregivers of individuals with chronic mental illness frequently exert a detrimental influence on daily living. Obsessive-Compulsive Disorder (OCD) is one of the long-standing, debilitating disorders that impacts the physical and mental health well-being due to its characteristics and progression. This study aims to look at how much stress caregivers feel, their QoL, and how they cope while caring for people with OCD compared to caregivers of healthy individuals, as well as exploring how these factors are connected in both groups. Methods: This research used a comparative and correlational research design. We used the purposive sampling method to collect a total of 100 samples, with 50 samples from each group. Results: The study groups were equivalent in all sociodemographic factors. Statistically significant differences (p<0.05) were seen in caregiving burden, QoL, and coping mechanisms. A negative correlation was identified between caregiver burden and the quality of life of caregivers of individuals with OCD, whereas no significant relationship was observed between caregiver burden and coping strategies. Conclusion: Providing care for an individual with OCD significantly affects health outcomes, adversely impacting the well-being and QoL of caregivers. The subjective and objective burdens faced by caregivers of individuals with OCD are significantly detrimental to their well-being and quality of life, resulting in adverse health effects while also fostering resilience in coping strategies.